(untitled) (Contemporary Journal of Social Science Review, 2025)
The podcasts have been an influential medium of dialogue, education, and entertainment in the digital media era. Podcasts in Pakistan are a distinctive space for an encounter of English and Urdu, thus it involves a projection of a conflux of more generalized sociolinguistic hierarchies and identity practices. The research explores the impact of English on Pakistani podcasts and how language is generally used to shape individual identity, authority and speakers perception by their audience. Based on a sociolinguistic framework, the paper will analyze linguistic behavior in some of the popular podcasts such as Happy Chirp, The Pakistan Experience, and Thought behind Things. It is a mixed-method study on the English code-mixing, code-switching and the different aspects used in it to indicate social status, education, and cosmopolitan identity. The findings point to the way English is not an easy piece of communication but an item of prestige and symbolic capital in the digital discourses of Pakistani podcasts. The paper contributes to the body of knowledge regarding the phenomena of language contact in the new media environment and brings the importance of the linguistic hybridity to mirror the current social and cultural changes of Pakistan.